2014
DOI: 10.1007/s12155-014-9566-x
|View full text |Cite
|
Sign up to set email alerts
|

PvNAC1 and PvNAC2 Are Associated with Leaf Senescence and Nitrogen Use Efficiency in Switchgrass

Abstract: Two full-length cDNAs encoding NAM, ATAF, and CUC (NAC)-family transcription factors (TFs) were isolated from two different cultivars of Panicum virgatum L. (switchgrass) and named PvNAC1 and PvNAC2. Phylogenetic analysis of PvNAC1 and PvNAC2 grouped them with NAC proteins involved in senescence in annual plant species. Transcript profiling revealed that both PvNAC1 and PvNAC2 are induced during leaf senescence. Expression of a PvNAC1-green fluorescent protein (GFP) fusion in plant cells revealed a nuclear loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 42 publications
1
15
0
1
Order By: Relevance
“…During soybean senescence, H 2 S and rhizobia enhanced the transcription of the GmNAC1 , GmNAC3 , GmNAC4 , GmNAC5 , and GmNAC6 genes and downregulated the expression of GmNAC2 in leaves (Figure f‐k). As previously reported, PvNAC1 and PvNAC2 were expected to improve nutrient use efficiency of switchgrass by genetic manipulation (Yang et al, ). Simultaneously, the functional grouping of SAG s in switchgrass indicated that transcription and protein degradation play a crucial role in regulating plant senescence.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…During soybean senescence, H 2 S and rhizobia enhanced the transcription of the GmNAC1 , GmNAC3 , GmNAC4 , GmNAC5 , and GmNAC6 genes and downregulated the expression of GmNAC2 in leaves (Figure f‐k). As previously reported, PvNAC1 and PvNAC2 were expected to improve nutrient use efficiency of switchgrass by genetic manipulation (Yang et al, ). Simultaneously, the functional grouping of SAG s in switchgrass indicated that transcription and protein degradation play a crucial role in regulating plant senescence.…”
Section: Discussionsupporting
confidence: 59%
“…TFs associated with aging are also indispensable in the coordinated control of shoot senescence and effective N remobilization. As a TF family, the NAC gene family plays a conserved role in plant leaf senescence (Hollmann, Gregersen, & Krupinska, ; Yang et al, ). For example, the expression of the transcription factor HvNAC026 and serine‐type protease SCPL51 was upregulated during senescence in barley flag leaves under standard N supply (Hollmann et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these module 3 genes was a NAC transcription factor encoded by Pavir.J16651 . This specific NAC (called PvNAC1) was demonstrated to impact leaf senescence in switchgrass [ 78 ], and is most similar to AtNAC29 , which has been implicated in leaf senescence in A. thaliana [ 79 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the square footage of the biorefinery that produces the fuel can have a major impact on sustainability, impacting the transportation radius for bringing biomass from the surrounding area 31 . Growth and nutrient-use advantages are being seen through inoculation with endophytic fungi 32 , and manipulation of transcription factor genes that are important for nutrient cycling during senescence may improve nutrient-use efficiency in perennial plants such as switchgrass 33 .…”
Section: Lignocellulosic Biofuelsmentioning
confidence: 99%